Book Review: Eating Her Curries and Kway: A Cultural History of Food in Singapore - Van , Penny (Penerbit Universiti Sains Malaysia (USM Press), 2015)
Nicole Tarulevicz opens her book about food in Singapore with a key question: How does food become its own form of rule-making? She ends the book with the observation that rules are central to life in Singapore. Between these two points, she brings to bear a wide range of evidence concerning food in this unique city state where the relation between food and nation is especially strong. Singapore is a society in which rules and regulations matter, a truly prescriptive society that monitors cultural heritage, the family and the body.